Avaliação da perda óssea alveolar em pacientes encaminhados à especialista em periodontia: estudo radiográfico - Kerbauy, Warley David [UNESP] (Universidade Estadual Paulista (Unesp), 1999)
The aim of this study was to evaluate the mean of alveolar bone loss (%) in radiographies of patients referred to specialist for periodontal treatment. Full mouth series of periapical radiographies (paralelism technique) were used. A total of 9808 proximal surfaces in 4804 teeth of 213 patients (90 males and 123 females), mean age, 44.3 years, were assessed. The alveolar bone loss was measured in relation to root lenght expressed as an average similar to Schei 's technique (1959) without the use of ruler. The references used were the distances cement-enamel juntion (CEJ) - alveolar crest (AC) and CEJ- dental apex taken with a digimatic caliper. The results showed that the mean values of alveolar bone loss (%ABL) was 22.39%. Men showed higher mean values of %ABL than women; the %ABL increased with the age, but the difference among age groups was no statistical significant (p>0.05); the mean values of %ABL of distal surfaces was higher than mesial surfaces (p<0.01), ríght quadrants exhibited higher %ABL values than left quadrants (p<0.01); maxillary sites showed mean values of %ABL higher than mandibular sites; the highest mean values of %ABL was found in molar group, followed by incisor groups, and premolar group; the canine group exhibited lower mean values of %ABL; the differences among the groups was considered statitistically significant (p<0.01). lt was suggested the usage of this technique in the dentistry offices and radiological services for the patient 's documentation and assortment and for later comparison about alveolar bone level

O objetivo deste estudo foi avaliar a porcentagem média de perda óssea alveolar (%MPOA) em radiografias de pacientes encaminhados a periodontista para tratamento. Foram empregadas séries de 14 radiografias periapicais, tomadas com a técnica do paralelismo, de 213 pacientes (noventa homens e 123 mulheres) com idade média de 44,3 anos e avaliamos 9608 superfícies proximais de 4804 dentes. A perda óssea alveolar foi dada como porcentagem média baseando-se na técnica de Schei et al. (1959). Também usamos os mesmos pontos de referência: distância junção esmalte-cemento à crista óssea alveolar e distância junção esmalte cemento ao ápice dentário, medidas com auxilio de paquímetro digital. Nossos resultados mostraram que a porcentagem média de perda óssea alveolar foi de 22,39%. Homens exibiram maior %MPOA que mulheres; a arcada superior exibiu %MPOA maior que a inferior; as superficies distais mostraram %MPOA maior que as mesiais; a %MPOA aumentou com a idade, embora as diferenças entre os grupos etários foram consideradas estatisticamente não significativas (p>0.05); a %MPOA foi maior nas proximais dos dentes dos hemiarcos direitos que dos esquerdos (p<0,05). A mais alta porcentagem média de perda óssea alveolar foi encontrada no grupo dos molares, seguida pelo grupo dos incisivos e grupo dos pré-molares; o grupo dos caninos exibiu a mais baixa %MPOA. As diferenças entre os grupos dentários foram consideradas estatisticamente significativas (p<0.01). Foi discutido o emprego desta técnica nos consultórios e clínicas radiográficas para documentação e classificação dos pacientes e para futuras comparações sobre nível ósseo alveolar
Keywords: Periodontia; Processo alveolar; Consultórios odontológicos; Radiografia dentária; Periodontics